Harmonization of Civil Law and Sharia Principles in the Validity of Murabahah Contracts - Novea Elysa Wardhani (JURNAL AKTA, 2026)
The rapid growth of Sharia-based financial institutions in Indonesia, particularly Sharia Savings and Financing Cooperatives (Koperasi Simpan Pinjam dan Pembiayaan Syariah, or KSPPS), has elevated the importance of murabahah financing as a primary product for community economic empowerment. However, the implementation of murabahah contracts at KSPPS faces significant legal challenges arising from the divergence between Indonesia's civil law framework and Islamic Sharia principles. This study aims to analyze the harmonization of civil law and Sharia principles in the validity and dispute resolution of murabahah contracts within KSPPS. Employing a normative legal research method, this study utilized three approaches: the statute approach, the conceptual approach, and the case approach. Legal materials were gathered from primary sources including statutory regulations (KUHPerdata, Law No. 21/2008 on Islamic Banking, Law No. 3/2006 on Religious Courts), DSN-MUI fatwas, and the Compilation of Sharia Economic Law (KHES), as well as secondary sources comprising legal journals and academic literature. The novelty of this research lies in its dual-perspective analysis that integrates civil law doctrines with Sharia normative standards to evaluate murabahah contract validity, particularly in the KSPPS institutional context. The study finds that murabahah contracts are valid under civil law provided they satisfy Article 1320 of the Civil Code, while Sharia validity requires compliance with DSN-MUI Fatwa No. 04/2000, especially the prerequisite of actual goods ownership by KSPPS prior to sale. Harmonization is achieved through dual legal drafting, inclusion of forum selection clauses referring to Religious Courts or BASYARNAS, and the recognition of DSN-MUI fatwas as material legal sources in dispute resolution. This research contributes to the formulation of better regulatory policies for integrating civil law and Sharia principles in Islamic cooperative finance.